Study on the Flow Field around Two Parallel Moving Bubbles and Interaction Between Bubbles Rising in CMC Solutions by PIV - 范文元 马友光 李小磊 李怀志 (Chinese journal of chemical engineering, 2009)
The flow fields surrounding two parallel moving bubbles rising from two identical orifices submerged in non-Newtonian fluid of carboxymethylcellulose （CMC） solution of three different mass concentration were measured experimentally by the use of particle image velocimetry （PIV）. The influences of gas flowrate, solution mass concentration, orifice interval and the angle between two bubble centers line and vertical direction on the flow field surrounding bubbles were discussed respectively by analyzing the velocity vector, velocity contours as well as individual velocity components. The results show that the liquid velocity both in front of two bubbles and behind increases with gas flowrate duo to shear-thinning effect of previous bubbles, whereas decreases with the increase of CMC concentration due to the increase of drag force acting on bubbles. The effect of the orifice interval on the flow field around two moving bubbles becomes gradually obvious as the interval becomes closer. Moreover, two adjacent side-by-side bubbles repulse each other during rising, leading to the practical interval between them increased somewhat above the orifice interval. When the distance between bubbles is less than the orifice interval 10 mm, the interaction between two neighboring bubbles changed from mutual repellence to attraction with the decrease of the angle of the line of linking two bubble centers to the vertical direction.